A Novel Approach Based on Two-Dimensional Correlation Spectroscopy to Determine the Stoichiometric Ratio of Two Substances Involved in Intermolecular Interactions. Issue 9 (September 2019) - Li, Xiaopei; Zeng, Yiwei; Deng, Gang; Xu, Yizhuang; Ozaki, Yukihiro; Noda, Isao; Wu, Jinguang
A novel technique called AOSD@Job's, combining asynchronous orthogonal sample design scheme (AOSD) with Job's method, is proposed to estimate the stoichiometric ratio of two substances that form a supramolecular aggregate under intermolecular interactions. First, a mathematical analysis was performed along with the procedure of the AOSD@Job's method. Then, the validity of the AOSD@Job's method was manifested by computer simulation on two model systems. Finally, the AOSD@Job's method was applied on two real chemical systems. The stoichiometric ratio between the coordination complex of Ni 2+ and ethylenediaminetetraacetic acid disodium salt (EDTA) was estimated to be 1.0. Benzyl alcohol (BA) and β-cyclodextrin (β-CD) were determined to form a 1 : 1 host–guest complex. These values were consistent with the values reported in the literature. Compared with the traditional Job's method, the AOSD@Job's method has an evident advantage since it is still valid even if all the peaks of the supramolecular aggregate severely overlap with the peaks of the substances that form the aggregate.